Long-term and persistent vocal plasticity in adult bats - Daria Genzel (Nature Portfolio, 2019)
Bats are long-lived animals that can produce a complex vocabulary of social communication calls. Here, the authors show that even in adulthood, bats retain the ability to adaptively introduce long-term modifications to their vocalizations, showing persistent vocal plasticity.